Penjatuhan Pidana Terhadap Pelaku Tindak Pidana Narkotika Di Pengadilan Negeri Pekanbaru Dihadapkan Pada Disparitas: Penjatuhan Pidana Terhadap Pelaku Tindak Pidana Narkotika Di Pengadilan Negeri Pekanbaru Dihadapkan Pada Disparitas - Dean, Lardson (Universitas Medan Area, 2024)
Research objective: the sentencing of perpetrators of narcotics crimes at the Pekanbaru District Court is faced with disparities; To formulate the inhibiting factors; To find ways to overcome obstacles. Research method: The type of research is sociological legal research; Research location: Pekanbaru District Court; data collection techniques: observation, structured interviews and document/library study; data analysis: qualitative. Results and conclusions: The sentencing of perpetrators of narcotics crimes at the Pekanbaru District Court is faced with disparities in fact that will still occur in 2022 and 2023. The inhibiting factors: Legal factors, law enforcement officers and the community. Efforts to overcome obstacles: First, legal factors: judges should minimize the disparities that occur, even though there must be disparities, they must still be positive; Judges should, in exercising their authority, pay attention to justice for the wider community; the application of law by judges based on various balances from legal and social aspects of jurisprudence beyond the limits of their authority. Second, the factor of law enforcement officers: it is best for prosecutors or advocates to take legal action against the judge's decision; it would be best for the police, prosecutors and courts to unite their perceptions in implementing the Article; It is best if the judge's particular considerations are accompanied by the principle of propriety so that the verdict made is in accordance with legal provisions. Third, community factors: It would be better for the public and other law enforcers to find out about the defendant's role in a criminal case so as not to question the judge's verdict too often; It is best for the defendant in the trial to continue and tell the truth about the Narcotics crime; It is best for the defendant not to commit any more narcotics crimes because his position as a recidivist will be taken into consideration by the judge in aggravating the sentence against him; The defendant should no longer try to cover up the crime he committed and admit his guilt.